Health problems of nursing workers in a public educational institution - Carolina Luiza Bernardes; Lucinda Helena da Silva de Vasconcelos; Silmar Maria da Silva; Patrícia Campos Pavan Baptista; Vanda Elisa Andres Felli; Marcelo Pustiglione; Ruth Munhoz; Thatiana Fernanda Coa (SciELO, 2014)
Objective: To identify the issues occurred with nursing workers through a Health Monitoring System for Nursing Workers (SIMOSTE) and to describe the consequences of those problems. Method: This is a quantitative, exploratory and descriptive study realized in a teaching hospital in the west region of the city of São Paulo. Results: From the SIMOSTE, 1.847 occurrences were registered in a six month period. Within the main occurrences, medical licenses, work related accidents with and without removals; psychiatric consultations and psychotherapy were highlighted. Conclusion: The data points out to the need for the development of new health vigilance actions to notify accidents and illness related to work, besides the prevention of issues.